Effects of ß-alanine supplementation on performance and body composition in collegiate wrestlers and football players - Kern, B. D.; Robinson, T. L. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to examine the effectiveness of ß-alanine as an ergogenic aid in tests of anaerobic power output after 8 weeks of high-intensity interval, repeated sprint, and resistance training in previously trained collegiate wrestlers (WR) and football (FB) players. Twenty-two college WRs (19.9 ± 1.9 years, age ± SD) and 15 college FB players (18.6 ± 1.5 years) participated in this double-blind, placebo-controlled study. Each subject ingested either 4 g·d-1 ß-alanine or placebo in powdered capsule form. Subjects were tested pre and posttreatment in timed 300-yd shuttle, 90° flexed-arm hang (FAH), body composition, and blood lactate after 300-yd shuttle. Although not statistically significant (p > 0.05) subjects taking ß-alanine achieved more desirable results on all tests compared to those on placebo. Performance improvements were greatest in the FB supplement group, decreasing 300 shuttle time by 1.1 seconds (vs. 0.4-second placebo) and increasing FAH (3.0 vs. 0.39 seconds). The wrestlers, both placebo and supplement, lost weight (as was the goal, i.e., weight bracket allowance); however, the supplement group increased lean mass by 1.1 lb, whereas the placebo group lost lean mass (-0.98 lb). Both FB groups gained weight; however, the supplement group gained an average 2.1-lb lean mass compared to 1.1 lb for placebo. ß-Alanine appears to have the ability to augment performance and stimulate lean mass accrual in a short amount of time (8 weeks) in previously trained athletes. Training regimen may have an effect on the degree of benefit from ß-alanine supplementation.